Bedside Tool for Predicting the Risk of Postoperative Atrial Fibrillation After Cardiac Surgery: The POAF Score. Issue 2 (24th March 2014) - Mariscalco, Giovanni; Biancari, Fausto; Zanobini, Marco; Cottini, Marzia; Piffaretti, Gabriele; Saccocci, Matteo; Banach, Maciej; Beghi, Cesare; Angelini, Gianni D.
Abstract : Background: Atrial fibrillation (AF) remains the most common complication after cardiac surgery. The present study aim was to derive an effective bedside tool to predict postoperative AF and its related complications. Methods and Results: Data of 17 262 patients undergoing adult cardiac surgery were retrieved at 3 European university hospitals. A risk score for postoperative AF (POAF score) was derived and validated. In the overall series, 4561 patients (26.4%) developed postoperative AF. In the derivation cohort age, chronic obstructive pulmonary disease, emergency operation, preoperative intra‐aortic balloon pump, left ventricular ejection fraction <30%, estimated glomerular filtration rate <15 mL/min per m 2 or dialysis, and any heart valve surgery were independent AF predictors. POAF score was calculated by summing weighting points for each independent AF predictor. According to the prediction model, the incidences of postoperative AF in the derivation cohort were 0, 11.1%; 1, 20.1%; 2, 28.7%; and ≥3, 40.9% ( P <0.001), and in the validation cohort they were 0, 13.2%; 1, 19.5%; 2, 29.9%; and ≥3, 42.5% ( P <0.001). Patients with a POAF score ≥3, compared with those without arrhythmia, revealed an increased risk of hospital mortality (5.5% versus 3.2%, P =0.001), death after the first postoperative day (5.1% versus 2.6%, P <0.001), cerebrovascular accident (7.8% versus 4.2%, P <0.001), acute kidney injury (15.1% versus 7.1%, P <0.001), renal replacement therapy (3.8% versus 1.4%, P <0.001), and length of hospital stay (mean 13.2 versus 10.2 days, P <0.001). Conclusions: The POAF score is a simple, accurate bedside tool to predict postoperative AF and its related or accompanying complications.